GEODETIC BASIS WHEN PERFORMING MARINE HYDROGRAPHIC MEASUREMENTS: GEODETIC BASIS WHEN PERFORMING MARINE HYDROGRAPHIC MEASUREMENTS - Stoykov, Evgeni (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Geodetic network is the set of permanently stabilized points on the earth's surface, the position of which is determined in a single coordinate and altitude system (X, Y and H) accepted in a given country. When creating geodetic networks, the basic principle from the "general to the private" must be respected, i.e. one must go from the "big to the small".